Tymczasowe aresztowanie i zatrzymanie w postępowaniu karnym - Murzynowski, Andrzej (Wydział Prawa i Administracji UAM, 1984)
It is in general commonly understood in literature that detention under remand is only a litigious coercive measure, which is designed to prevent defendants' avoidance of sentence and carrying out the penalty. In reality however, it serves certain extrajudicial functions in all countries as general and individual crime prevention. It is an undesired fact transforming the detention under remand in a peculiar means of repression and causing too extensive use of that drastic measure. This is also a phenomenon violating the principle of presumption of the accused innocence. The grounds of application of the detention have to be therefore essentially limited to reasonable suspection of defendants (suspect's) avoidance of administration of justice. The only exception has to be extended on preventing the defendant from committing a new severe offence against life, health or public safety. Besides, the grounds for the detention under remand ought to be more precisely formulated land and the explicit duty to quote detailed reasons for the detention's application in the decision has to be introduced. In case of severe offences (liable to minimum five years of punishment) a reference to a prospective long term confinement might be sufficient reasons unless circumstances occur excluding the suspection of defendant's avoiding administration of justice (eg. his invalidism). The detention under remand should be decided exclusively by a judicial organ (court, examining magistrate) which is independent and impartial. Prosecutor is deprived of those qualities as he is acting under conditions of hierarchical subordination and performs functions of prosecuting side in criminal proceedings. Moreover, vesting judicial organs with the sole competence of applying that means would be entirely conformable to art. 9 sec. 3 of the International Covenant of Civil and Political Rights, ratified by Poland in 1977. Limitations in realizing the right to defense by the detainees in course of the preparatory proceedings are known. It is mostly the case of subjecting suspect's (possibility to consult his counsel for the defense to prosecutor's consent and searching the possibility of counsels presence during suspect's interrogation. In this respect substantial changes are needed. A problem of applying detention under remand both in the preparatory proceedings and throughout the whole of criminal proceedings is not properly solved in the respect of time limits. They do not have a character of deadlines in the preparatory stadium and they are lacking in the further stages of the proceedings. The similar phenomenon is after all observed in many countries. In the result there are instances of lengthy deprivation of liberty of persons Who have! not yet been sentenced. It therefore seems that a definitive period of application of detention under remand should be statutorily limited to one year in the preparatory proceedings and to two years until passing a sentence in the first instance court. Detention in custody is another acute although short term means of depriving of liberty which is in the discretion of civic police (militia). It is most extensively applied and seldom controlled both by judicial organs and by prosecutor. In this respect more precise statutory provisions are needed to strengthen legality of use of that coericive mean and introduce a judicial review of the practice. In this aim a requirement of issuing a motivated writ of detention in custody should be introduced, and detainees must be vested with the right to claim their immediate bringing to court, lodging a complaint against groundless detention as well as adopting a counsel for defense.
Detention under remand and detention is custody in criminal procedure